Hubungan antara Persepsi dan Kepuasan Pasien Jaminan Kesehatan Nasional (JKN) terhadap Kualitas Pelayanan Di Rumah Sakit - Nor Tri Astuti Wahyuningsih; Diajeng Nimasayu Ezra Puspa; Daniel Budi Wibowo (STIKES Ngesti Waluyo, 2025)
Patients coming to the hospital expect satisfactory and quality service. If the patient’s perceived service does not match their expectations, they might choose another hospital. The study aims to analyse the correlation between perception and patient satisfaction towards service quality. The study used a quantitative research method with an analytic and cross-sectional approach. The population was all outpatient JKN patients at a private hospital in Semarang, who visited the hospital in June 2024. The average daily visit was 468 patients, and the sample size was 215 respondents, taken by simple random sampling. The results showed a significant, favourable correlation between JKN patients’ perceptions and satisfaction with service quality. The better the patient’s perception of the service quality, the higher the level of patient satisfaction. The conclusion is that there is a very strong correlation between the perceptions of service quality and satisfaction. The implication is that there is a need to maintain and improve the service quality in hospitals.